Figuring One’s Calling: A Lukan Passion Theology of Vocation in Dialogue with Karl Barth - Erickson, Amy J. (Journal of theological interpretation, 2023)
This article contends that a figural reading of Luke’s passion narrative, influenced by Barth’s account of vocation, offers a heuristic for discerning contemporary callings. The first part of this study examines Barth’s theology of vocation. For Barth, one’s vocation is a dialectic of the concrete circumstances of the disciple and the dynamic, event-like nature of the call itself. Together, a disciple’s vocation is primarily a form of witness to the Christ who calls. The article then deploys Barth’s account of vocation to inform a figural reading of Luke’s passion narrative. This reading generates a renewed perception of prevailing vocational forms in the present.